2018
DOI: 10.1136/jmedgenet-2018-105482
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal evaluation of SMN levels as biomarker for spinal muscular atrophy: results of a phase IIb double-blind study of salbutamol

Abstract: BackgroundSpinal muscular atrophy (SMA) is an autosomal recessive neuromuscular disorder, due to the loss of function of the survival motor neuron (SMN1) gene. The first treatment for the condition, recently approved, is based on the reduction of exon 7 skipping in mRNAs produced by a highly homologous gene (SMN2). The primary objective of the present study was to evaluate the applicability of the dosage of SMN gene produts in blood, as biomarker for SMA, and the safety of oral salbutamol, a beta2-adrenergic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 35 publications
0
22
0
1
Order By: Relevance
“…Similar results have been seen with salbutamol; a compound that increases SMN2 full length transcript and SMN protein. In this study, a subjective improvement of motor function was noted in all patients with a statistically significant improvement in validated functional scores in a proportion of patients (26). This suggests target engagement and a potential method of tracking treatment response.…”
Section: Circulating Biomarkersmentioning
confidence: 49%
“…Similar results have been seen with salbutamol; a compound that increases SMN2 full length transcript and SMN protein. In this study, a subjective improvement of motor function was noted in all patients with a statistically significant improvement in validated functional scores in a proportion of patients (26). This suggests target engagement and a potential method of tracking treatment response.…”
Section: Circulating Biomarkersmentioning
confidence: 49%
“…While the reported CK/Crn dynamics suggest therapy response in our nusinersen-treated cohort, Tiziano et al reported an increase of CK associated with increasing SMN2-full length transcripts in SMA patients treated with salbutamol in a clinical trial. 45 Here, CK values were evaluated as part of safety assessment, because salbutamol and other beta2 agonists are known to increase CK levels 46 regardless of the underlying disease (also patients without neuromuscular diseases 47,48 ). This is of interest, as it shows that CK is influenced by different factors, which have to be properly controlled in further prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials which could address this issue require long durations and robust clinical outcome measures, drawing attention to the need for biomarkers which are sensitive to changes in disease progression and/or response to disease modifying agents [120]. Unlike studies in infants and children with SMA, in which circulating neurofilaments are emerging as potential measures to assess disease progression and response to nusinersen treatment [121], no studies in adults with SMA have yielded a robust, reliable measurement [86,88,[122][123][124][125][126]. A potential complexity in trying to detect elevated markers of axonal degradation in adults with SMA is again the slow rate of progression.…”
Section: Discussionmentioning
confidence: 99%